Do bank bailouts affect the provision of trade credit?11All errors are our own. The views expressed in this paper are solely those of the authors and should not be interpreted as reflecting the views of the Board of Governors or the staff of the Federal Reserve System - Nordén, Lars; Udell, Gregory F.; Wang, Teng (Journal of Corporate Finance, 2020)
We document that borrowers of banks that received capital support under TARP/CPP significantly increased their quarterly provision of trade credit (accounts receivable) during the crisis by 5.2%, while borrowers of other banks did not. The effect is strongest in 2008Q4, and larger for pre-crisis riskier, growth-oriented and bank-dependent firms and for firms that borrow from pre-crisis smaller, less profitable and better capitalized CPP banks. Our difference-in-differences analysis shows that the effect is caused by CPP and not by heterogeneity between firms, banks and time periods. Our study provides novel evidence that suggests a beneficial multiplier effect of bank bailouts.